2015
DOI: 10.19183/how.22.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Needs Analysis in an EFL Program for University Professors

Abstract: This study sets out to investigate professors' needs from an English as a foreign language program in a public university regarding demands, interests, and lacks based on the methodology of needs analysis. Data collected through a survey, focus groups, and individual interviews showed that professors need to meet the institutional language policy for contractual and academic reasons. Additionally, data revealed their desire to learn English to communicate in both academic and non-academic settings. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
(17 reference statements)
5
8
0
Order By: Relevance
“…Most of them agreed that they preferred to do tasks in groups instead of doing the task individually, in pairs, and whole class work. These results accord with the findings of Bedoya, Valencia, & Montoya (2015). They found that the participants feel more engaged in group activities rather than individual work.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most of them agreed that they preferred to do tasks in groups instead of doing the task individually, in pairs, and whole class work. These results accord with the findings of Bedoya, Valencia, & Montoya (2015). They found that the participants feel more engaged in group activities rather than individual work.…”
Section: Discussionsupporting
confidence: 91%
“…The students also confessed that they feel that their English proficiency is elementary. The findings keep in line with Bedoya, Valencia, & Montoya (2015) who affirm that the participants have very low level in English. In addition, the findings of this research corroborate the findings of Fard-Kashani & Jahromi (2015) that claim that the undergraduate students of computer and engineering suffered from low English proficiency.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, as attested by the high percentages of those who strongly agreed, all the other writing sub-skills are considered important. These results match with what was found by Vahed (2017) and Bedoya et al (2015) who concluded that their subjects needed academic writing courses to prepare them to write scientific papers.…”
Section: What Are the Most Important Academic Sub-skills For The Tas?supporting
confidence: 91%
“…These results agree with what was revealed by Vahed (2017), who concluded that his subjects needed EAP courses to prepare them for academic study. The results are also in line with Bedoya et al (2015) who found that their students needed to be proficient in English to communicate with it.…”
Section: Why Do the Tas At The U Of K Need The English Language?supporting
confidence: 88%
See 1 more Smart Citation